2008
DOI: 10.1073/pnas.0804566105
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalyst activity in nonaqueous environments correlates with centisecond-range protein motions

Abstract: Recent studies exploring the relationship between enzymatic catalysis and protein dynamics in the aqueous phase have yielded evidence that dynamics and enzyme activity are strongly correlated. Given that protein dynamics are significantly attenuated in organic solvents and that proteins exhibit a wide range of motions depending on the specific solvent environment, the nonaqueous milieu provides a unique opportunity to examine the role of protein dynamics in enzyme activity. Variable-temperature kinetic measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Protein motions play an important role in myriad protein functions, including catalysis and signaling (23); therefore, altered enzyme dynamics in organic solvents can have a detrimental effect on biocatalytic activity. Restricted motion has been strongly correlated with enzyme activity, or lack thereof, in organic solvents (24)(25)(26). Structural data available for proteins in organic solvents are limited when compared with the vast array of complete structures available for proteins in water.…”
Section: Unnatural Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein motions play an important role in myriad protein functions, including catalysis and signaling (23); therefore, altered enzyme dynamics in organic solvents can have a detrimental effect on biocatalytic activity. Restricted motion has been strongly correlated with enzyme activity, or lack thereof, in organic solvents (24)(25)(26). Structural data available for proteins in organic solvents are limited when compared with the vast array of complete structures available for proteins in water.…”
Section: Unnatural Conditionsmentioning
confidence: 99%
“…Overall or local changes in the secondary or tertiary structure of proteins in organic solvents are typically detected using Fourier transform infrared spectroscopy (27), circular dichroism (CD) (28), fluorescence, and electron spin resonance spectroscopy (29,30), but there are few reports of data collected at the atomic level. NMR has the ability to provide higher-resolution information but to date has provided only bulk-average data (25), surface water properties (31), or single-site information (26). In one published high-resolution study, a crystal structure of the protease subtilisin Carlsberg formed in water and soaked in acetonitrile showed almost no structural change from the aqueous structure (32).…”
Section: Unnatural Conditionsmentioning
confidence: 99%
“…Conversely, in non-aqueous media, lipases can use other nucleophiles, such as methanol, to catalyse esterification and transesterification reactions [2][3][4][5][6][7][8][9][10][11][12][13] , although the explicit removal of water is not often a priority. Typically, enzyme reactions performed in organic solvents still contain a hydration layer at the surface of the protein, and the pervasiveness of the solvent in these examples highlights the requirement for a substrate delivery medium [14][15][16][17][18][19][20][21][22][23][24][25] . There have also been reports of lipase catalysis where the reaction proceeds with solvent quantities of one of the reagents 3,12,13 , where the lipases are typically present as either a lyophilized powder 12,13,26 , or immobilized on a substrate 2,3,8,10,27,28 , but there are no examples of molecularly dispersed enzymes catalysing reactions in the complete absence of a solvent.…”
mentioning
confidence: 99%
“…The implications of theses findings is that while the enzyme becomes more rigid by the removal of its internal water molecules over a 96 hour period, the active site polarity should decrease (as suggested by our fluorescence data) and disruption of the oxyanion hole might reduce the enzyme’s ability to stabilize the tetrahedral intermediates, decreasing both V max and K M , as shown by the results here presented. Furthermore, a decrease in the polarity of the active site and disruption of the oxyanion hole could lead to reorientation of the bound substrate [12] or allow the substrate to bind in a less restricted fashion, letting it move more freely, as it has been shown on previous studies involving EPR spectroscopy [9, 31]. In short, one interpretation that is emerging from these studies is that changes in active site polarity during prolonged exposure to organic solvents are the major cause of the observed decrease in enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to discuss some of these results since the effects that are linked to enzyme activity are enzyme flexibility and active-site polarity, both related to our work. Eppler et al 19 F NMR active site polarity studies show that increasing the salt concentration (NaCl, NaF, KCl and KF) in hexane from 0 to 98% did not augment enzyme polarity (while enzyme activity was increased), concluding that changes in polarity do not affect enzyme activity [31]. On a similar and more recent study however, it was concluded that active site polarity and hydration do affect enzyme activity, but that this effect was also dependent on the solvent used [32].…”
Section: Discussionmentioning
confidence: 99%